The Demographic Profile, Etiology and Outcomes of Acute Postoperative Endophthalmitis - Dewi, Amalia Zahra; Sofia, Ovi (Indonesian Vitreoretinal Society, 2025)
Introduction: To describe patient characteristics, bacterial patterns, management, and outcomes of therapy in patients with acute postoperative endophthalmitis. Method: This observational, descriptive study was conducted at Dr. Saiful Anwar General Hospital in Malang, Indonesia, between 2020 and 2024, involving all patients with newly diagnosed acute postoperative endophthalmitis with periode follow up patient's initial visit, on day 7, and on day 28 following treatment Results: A total of 74 patients were included in the study. The majority were male (51.3%), with a mean age of 61.57 ± 11.54 years. The most common comorbid was diabetes mellitus (16.2%). The etiology was most commonly due to gram-negative bacilli (13%), and phacoemulsification was the most common surgical procedure associated with endophthalmitis (74%). Quinolones exhibited the highest sensitivity. The most common management was a combination of medical and surgical treatments, including intravitreal antibiotic injections (59%) and combination of intravitreal antibiotic injections and pars plana vitrectomy (PPV) (18%) . The visual acuity outcomes revealed that 45,9% patients experienced improvement. Conclusion: The incidence of endophthalmitis increases with advancing patient age, correlating with a higher frequency of cataract surgeries performed. Current management outcomes for endophthalmitis are favorable, reflecting improvements aligned with updated clinical guidelines. The comprehensive management of endophthalmitis will result in an improved visual outcome.